Numerical Solution of 2-point Boundary Value Problem by Subdivision Scheme - Kanwal, G.; Ghaffar, A.; Hafeezullah, M. M.; Manan, S. A.; Rizwan, M.; Rahman, G. (Communications in Mathematics and Applications, 2019)
A numerical approximating collocation algorithm is formulated that is based on binary 6-point approximating subdivision scheme to generate the curves. It is examined that the scheme is generating more smooth continuous solutions of the problems. Numerical example is given to illustrate the algorithm with its graphically representation.